Meningkatkan Kualitas Air Irigasi dengan Menggunakan Tanaman Kayu Apu (Pistia stratiotes L.) dan Tanaman Azolla (Azolla sp.) di Subak Sembung, Peguyangan, Denpasar - NI WAYAN MAYA SARI; I WAYAN DIARA; NI MADE TRIGUNASIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Increasing Irrigation Water Quality Using Pistia Plant (Pistia stratiotes L.)and Azolla Plant (Azolla sp.) in Subak Sembung, Peguyangan, DenpasarThe research aimed to determine the quality of Subak Sembung’s irrigation water, investigate the influence of Pistia and Azolla plant as well as identifying which of the plant is more effective in improving the quality of the irrigation water. The research consisted of several stages including; collecting secondary data followed by conducting water purification experiment using Pistia and Azolla plant. The sample of the water was analyzed in Analytic Laboratory and MIPA Faculty Laboratory of Udayana University.The result of the study showed that before Subak Sembung’s irrigation water was given treatments has been contaminated by Cadmium (Cd) while two other parameters – Boron (B) and Arsen (As) cannot be found in the water. The increase was shown in the level of TSS, pH, BOD and COD while the decrease was shown in the level of TDS, Cadmium (Cd), Chromium (Cr) and total coli form. Pisita plant is more capable in reducing the level of Chromium metal (Cr) compared to Azolla plant while Azolla plant is better at reducing the level of Cadmium metal (Cd). However, a further research on heavy metal absorption using Pistia and Azolla plant is necessary.